A Biomass‐Derived Non‐Noble Cobalt Catalyst for Selective Hydrodehalogenation of Alkyl and (Hetero)Aryl Halides. Issue 37 (30th June 2017) - Sahoo, Basudev; Surkus, Annette‐Enrica; Pohl, Marga‐Martina; Radnik, Jörg; Schneider, Matthias; Bachmann, Stephan; Scalone, Michelangelo; Junge, Kathrin; Beller, Matthias
Abstract: Hydrodehalogenation is a straightforward approach for detoxifications of harmful anthropogenic organohalide‐based pollutants, as well as removal of halide protecting groups used in multistep syntheses. A novel sustainable catalytic material was prepared from biowaste (chitosan) in combination with an earth‐abundant cobalt salt. The heterogeneous catalyst was fully characterized by transmission electron microscope, X‐ray diffraction, and X‐ray photoelectron spectroscopy measurements, and successfully applied to hydrodehalogenation of alkyl and (hetero)aryl halides with broad scope (>40 examples) and excellent chemoselectivity using molecular hydrogen as a reductant. The general usefulness of this method is demonstrated by successful detoxification of non‐degradable pesticides and fire retardants. Moreover, the potential of the catalyst as a deprotection tool is demonstrated in a multistep synthesis of (±)‐peronatin B (alkaloid). Abstract : One man's trash is another man's treasure : A sustainable heterogeneous catalyst was prepared from chitosan biomass and earth‐abundant cobalt salt. Using molecular hydrogen, the catalyst achieved hydrodehalogenation of a broad variety of organic halides (>40 examples) with excellent chemoselectivity; including harmful pesticides and a fire retardant.